Towards novel antimicrobials - CHIARA COSTANZO (2023)
The widespread use of antimicrobials has led to the development of resistance to most known active compounds. This has led to the necessity to discover new drugs or adopt new strategies in order to overcome resistance. Benzimidazole is a building block commonly found in pharmaceuticals. It is well known for its antimicrobial, antiviral, anticancer and antiulcer properties as well as antihistaminic, anticoagulant and anti-inflammatory activity. In order to overcome bacterial resistance to β-lactam antibiotics, an in-silico screening of the designed benzimidazoles was undertaken leading to a library of compounds with good predicted binding affinity for lytic transglycosylases, a group of enzymes involved in the induction of β-lactamases. Strategies for extending the benzimidazole nucleus were developed, leading to the synthesis of 150 compounds. The synthetic strategies explored led to the discovery of a N1 / C2 competition with the recovery of two products in a one pot synthesis. This allowed formation of N1-alkylated and 2-phenyl analogues as well as 2-pyrrole and 2-thiophene derivatives. The consolidation of the most suitable synthetic method for extending the core in position number 2 furtherly led to bis-benzimidazoles and indole-benzimidazole hybrids. The benzimidazoles synthesized were screened against E. coli, S. aureus and P. aeruginosa, leading to the identification of hit compounds with antibacterial effect, one of them having a comparable activity to ampicillin. Furthermore, as benzimidazoles are well known for targeting tubulin, an attractive target for antiparasitic drugs, the effect of the benzimidazoles against S. mansoni was investigated in order to establish their activity against parasitic worms. A hit compound was selected for affecting both phenotype and motility in adult worms. Structure-activity relationship considerations have been proposed and the most promising core modifications leading to antibacterial or antiparasitic activity have been highlighted. Overall, this work has identified new antibacterial and antihelminthic hit compounds that can form the basis for future work to improve potency, confirm the compounds’ targets, and investigate other important medicinal chemistry considerations such as selectivity and ADME properties.